COMPARATIVE ANALYSIS OF INDONESIA AND THAILAND STUDENTS' MATHEMATICAL THINKING ABILITY - Agustiana, Anisa; Arisetyawan, Andika; -, Supriadi; Anusaen, Krittika (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2023)
This research aims to compare mathematical thinking abilities between elementary school students in Tangerang, Indonesia and Mahasarakham, Thailand. The method used in this research is a comparative study which is carried out by comparing the answers to mathematics test questions given to the research subjects, namely elementary school students in grades 3 and 5. The main aim of this research is to find out the factors that cause differences in the answers of each student. The results of this research show that there are differences between students in answering mathematics test questions caused by variations in the level of intelligence within one class, including certain aspects such as understanding concepts, problem solving skills, and abstract thinking abilities. Thus, each student's mathematical thinking ability can be influenced by specific factors that include their cognitive characteristics and mathematical development. Even though students' answers vary through different processes, this shows the uniqueness of the approach and mathematical thinking strategies applied by each student in completing the test. It is hoped that this research can make a contribution to the world of education, especially in designing learning plans that are tailored to the characteristics and abilities of each student